Analyzing the local basis set superposition error for CO adsorbed on rutile(110). Issue 2 (6th August 2020) - Dononelli, Wilke; Klüner, Thorsten
Abstract: One of the main tasks of quantum chemistry is to predict total energies for a given system within an almost nonapproximate method for a complete basis set. Unfortunately, although computational power is growing, approximate methods such as MP2 or CCSD(T) still have to be used as higher‐level methods such as full CI are computationally too demanding. Nevertheless, when using these approximations, at least an almost‐complete basis set should be used in order to avoid errors from basis set superposition or incompleteness. The aim of this work is to introduce a new method to analyze the local basis set superposition error (LBSSE) using local counterpoise corrections in order to converge a basis set for a given compound. Using this approach, we are able to define a basis set composition for a CO molecule adsorbed on rutile(110), which can be regarded as complete. In the presented work, CO adsorbed on rutile(110) and CO2 adsorbed on a model Ti3 O9 cluster will be used as case examples. Therefore, in addition to a new LBSSE analysis method, adsorption energies of CO on rutile(110) at the MP2 and CCSD levels of theory are presented. Abstract : When adsorption energies at higher levels of theory such as CCSD are calculated, the choice of an accurate basis set is crucial. If the basis is too small, BSSE and BSIE will affect the results. In this work, a method for analyzing the local BSSE is introduced that helps to achieve basis set convergence. MP2 adsorption energies of CO adsorbed on rutile(110) are presented together with CCSD adsorption energies utilizing the method of local increments.